Comparative Study on Plant Latex Particles and Latex Coagulation in Ficus benjamina, Campanula glomerata and Three Euphorbia species - Bauer, Georg (PLoS One, 2014)
Among latex-producing plants, mainly the latex of Hevea brasiliensis has been studied in detail so far, while comprehensive comparative studies of latex coagulation mechanisms among the more than 20,000 latex-bearing plant species are lacking. In order to give new insights into the potential variety of coagulation mechanisms, the untreated natural latices of five latex-bearing plants from the families Euphorbiaceae, Moraceae and Campanulaceae were visualised using Cryo-SEM and their particle size compared using the laser diffraction method. Additionally, the laticifers of these plants species were examined in planta via Cryo-SEM. Similar latex particle sizes and shape were found in Ficus benjamina and Hevea brasiliensis. Hence, and due to other similarities, we hypothesize comparable, mainly chemical, coagulation mechanisms in these two species, whereas a physical coagulation mechanism is proposed for the latex of Euphorbia spp. The latter mechanism is based on the huge amount of densely packed particles that after evaporation of water build a large surface area, which accelerates the coagulation procedure.